Anterior cingulate hyperactivations during negative emotion processing among men with schizophrenia and a history of violent behavior - Tikàsz A; Potvin S; Lungu O; Joyal C; Hodgins S; Mendrek A; Dumais A (Neuropsychiatric Disease and Treatment)
Andràs Tikàsz,1,2 Stéphane Potvin,1,2 Ovidiu Lungu,2–4 Christian C Joyal,5,6 Sheilagh Hodgins,2,5 Adrianna Mendrek,1,7 Alexandre Dumais1,2,5 1Centre de recherche de l’Institut Universitaire en Santé Mentale de Montréal, 2Department of Psychiatry, University of Montreal, 3Centre de recherche de l’Institut Universitaire de Gériatrie de Montréal, 4Centre for Research in Aging, Donald Berman Maimonides Geriatric Centre, 5Institut Philippe-Pinel de Montréal, 6Department of Psychology, Université du Québec à Trois-Rivières, Trois-Rivières, 7Department of Psychology, Bishop’s University, Sherbrooke, QC, Canada Background: Evidence suggests a 2.1–4.6 times increase in the risk of violent behavior in schizophrenia compared to the general population. Current theories propose that the processing of negative emotions is defective in violent individuals and that dysfunctions within the neural circuits involved in emotion processing are implicated in violence. Although schizophrenia patients show enhanced sensitivity to negative stimuli, there are only few functional neuroimaging studies that have examined emotion processing among men with schizophrenia and a history of violence. Objective: The present study aimed to identify the brain regions with greater neurofunctional alterations, as detected by functional magnetic resonance imaging during an emotion processing task, of men with schizophrenia who had engaged in violent behavior compared with those who had not. Methods: Sixty men were studied; 20 with schizophrenia and a history of violence, 19 with schizophrenia and no violence, and 21 healthy men were scanned while viewing positive, negative, and neutral images. Results: Negative images elicited hyperactivations in the anterior cingulate cortex (ACC), left and right lingual gyrus, and the left precentral gyrus in violent men with schizophrenia, compared to nonviolent men with schizophrenia and healthy men. Neutral images elicited hyperactivations in the right and left middle occipital gyrus, left lingual gyrus, and the left fusiform gyrus in violent men with schizophrenia, compared to the other two groups. Discussion: Violent men with schizophrenia displayed specific increases in ACC in response to negative images. Given the role of the ACC in information integration, these results indicate a specific dysfunction in the processing of negative emotions that may trigger violent behavior in men with schizophrenia. Keywords: schizophrenia, violence, negative emotions, salience, anterior cingulate cortex, fMRI